2020
DOI: 10.1088/2632-959x/abb715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetite and titania nanoparticles on properties of transformer insulating oil

Abstract: Transformer oil-based nanofluids have become popular research topic due to their enhanced dielectric and thermal properties. Considering the sustainability aspects of extending the life of transformer oil, it is imperative to conduct research on the effect of transformer oil with nanofillers. In the present work, the influence of conducting magnetite (Fe3O4), semiconducting titania (TiO2) nanoparticles and combination of Fe3O4 and TiO2 nanoparticles (multi-nanoparticle) on AC breakdown voltage are investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…5, the representative characterization techniques for TiO 2 NPs and oil-based TiO 2 NFs are demonstrated. 20,34,43–47…”
Section: Preparation Characterization and Stabilization Mechanism Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…5, the representative characterization techniques for TiO 2 NPs and oil-based TiO 2 NFs are demonstrated. 20,34,43–47…”
Section: Preparation Characterization and Stabilization Mechanism Of ...mentioning
confidence: 99%
“…The three above-mentioned studies reported in the literature investigated accelerated aging NFs. In addition, Pillai et al 46 prepared 0.01 wt% TiO 2 NFs using an oil which had been naturally aged for 5 years as the base oil. In comparison to the aged base oil, the AC BDV of NFs increased by 15%.…”
Section: Anticipated Properties Of Insulating Nfsmentioning
confidence: 99%
See 1 more Smart Citation